Association of early phenotypic behavioral alterations in human alpha-synuclein overexpressing transgenic rats with alpha-synuclein/huntingtin/amyloid-beta protein cross-seeding - Moceri, Sandra; Canneva, Fabio; Habermeyer, Johanna; Dobner, Julia; Schulze-Krebs, Anja; Puchades, Maja; Bjaalie, Jan G.; Kohl, Zacharias; Winkler, Jürgen; Timotius, Ivanna; Eskofier, Björn; Schilling, Stephan; et al. (Advances in Alzheimer's and Parkinson's Therapies an AAT-AD/PD Focus Meeting, 2018)

Comprehensive phenotyping revealed transient startle response reduction and histopathological gadolinium localization to perineuronal nets after gadodiamide administration in rats - Habermeyer, Johanna; Boyken, Janina; Harrer, Julia; Canneva, Fabio; Ratz, Veronika; Moceri, Sandra; Admard, Jakob; Casadei, Nicolas; Jost, Gregor; Bäuerle, Tobias; Frenzel, Thomas; Schmitz, Christoph; et al. (Scientific Reports, 2020)
Gadolinium based contrast agents (GBCAs) are widely used in clinical MRI since the mid-1980s. Recently, concerns have been raised that trace amounts of Gadolinium (Gd), detected in brains even long time after GBCA application, may cause yet unrecognized clinical consequences. We therefore assessed the behavioral phenotype, neuro-histopathology, and Gd localization after repeated administration of linear (gadodiamide) or macrocyclic (gadobutrol) GBCA in rats. While most behavioral tests revealed no difference between treatment groups, we observed a transient and reversible decrease of the startle reflex after gadodiamide application. Residual Gd in the lateral cerebellar nucleus was neither associated with a general gene expression pathway deregulation nor with neuronal cell loss, but in gadodiamide-treated rats Gd was associated with the perineuronal net protein aggrecan and segregated to high molecular weight fractions. Our behavioral finding together with Gd distribution and speciation support a substance class difference for Gd presence in the brain after GBCA application.
CRIS-Team WoS Importer:2021-01-22

Early postnatal behavioral, cellular, and molecular changes in models of Huntington disease are reversible by HDAC inhibition - Siebzehnrubl, Florian A.; Reber, Kerstin A.; Urbach, Yvonne K.; Schulze-Krebs, Anja; Canneva, Fabio; Moceri, Sandra; Habermeyer, Johanna; Achoui, Dalila; Gupta, Bhavana; Steindler, Dennis A.; Stephan, Michael; Huu Phuc Nguyen,; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2018)
Huntington disease (HD) is an autosomal dominant neurodegenerative disorder caused by expanded CAG repeats in the huntingtin gene (HTT). Although mutant HTT is expressed during embryonic development and throughout life, clinical HD usually manifests later in adulthood. A number of studies document neurodevelopmental changes associated with mutant HTT, but whether these are reversible under therapy remains unclear. Here, we identify very early behavioral, molecular, and cellular changes in preweaning transgenic HD rats and mice. Reduced ultrasonic vocalization, loss of prepulse inhibition, and increased risk taking are accompanied by disturbances of dopaminergic regulation in vivo, reduced neuronal differentiation capacity in subventricular zone stem/progenitor cells, and impaired neuronal and oligodendrocyte differentiation of mouse embryo-derived neural stem cells in vitro. Interventional treatment of this early phenotype with the histone deacetylase inhibitor (HDACi) LBH589 led to significant improvement in behavioral changes and markers of dopaminergic neurotransmission and complete reversal of aberrant neuronal differentiation in vitro and in vivo. Our data support the notion that neurodevelopmental changes contribute to the prodromal phase of HD and that early, presymptomatic intervention using HDACi may represent a promising novel treatment approach for HD.
EVALuna2:36091

Gene-dosage- and sex-dependent differences in the prodromal-Like phase of the F344tgHD rat model for Huntington disease - Ratz-Wirsching, Veronika; Habermeyer, Johanna; Moceri, Sandra; Harrer, Julia; Schmitz, Christoph; von Hörsten, Stephan (Frontiers in Neuroscience, 2024)
In Huntington disease (HD) the prodromal phase has been increasingly investigated and is currently in focus for early interventional treatments. Also, the influence of sex on disease progression and severity in patients is under discussion, as a sex-specific impact has been reported in transgenic rodent models for HD. To this end, we have been studying these aspects in Sprague Dawley rats transgenic for HD. Here, we took up on the congenic F344tgHD rat model, expressing a fragmented Htt construct with 51 CAG repeats on an inbred F344 rat background and characterized potential sexual dimorphism and gene-dosage effects in rats during the pre-symptomatic phase (1–8 months of age). Our study comprises a longitudinal phenotyping of motor function, emotion and sensorimotor gating, as well as screening of metabolic parameters with classical and automated assays in combination with investigation of molecular HD hallmarks (striatal cell number and volume estimation, appearance of HTT aggregates). Differences between sexes became apparent during middle age, particularly in the motor and sensorimotor domains. Female individuals were generally more active, demonstrated different gait characteristics than males and less anxiolytic-like behavior. Alterations in both the time course and affected behavioral domains varied between male and female F344tgHD rats. First subtle behavioral anomalies were detected in transgenic F344tgHD rats prior to striatal MSN cell loss, revealing a prodromal-like phase in this model. Our findings demonstrate that the congenic F344tgHD rat model shows high face-validity, closely resembling the human disease’s temporal progression, while having a relatively low number of CAG repeats, a slowly progressing pathology with a prodromal-like phase and a comparatively subtle phenotype. By differentiating the sexes regarding HD-related changes and characterizing the prodromal-like phase in this model, these findings provide a foundation for future treatment studies.
CRIS-Team Scopus Importer:2024-03-01
Keywords: behavioral phenotyping; gene-dosage; Huntington disease; prodrome; sex differences; striatal atrophy

Rodent’s Stride Length Depends on Body Size: Implications for CatWalk Assay - Timotius, Ivanna; Moceri, Sandra; Plank, Anne-Christine; Habermeyer, Johanna; Canneva, Fabio; Casadei, Nicolas; Riess, Olaf; Winkler, Jürgen; Klucken, Jochen; Eskofier, Björn; von Hörsten, Stephan (Measuring Behavior 2018, 2018)
The analysis of gait is an essential part of rodent phenotyping. Regarding the complex nature of walking, preclinical gait analysis is normally based on several gait parameters (which have been progressively developed [1,2] in recent years) including the animal’s stride length, body speed, support, etc. The stride length is altered in several diseases [3–5] and this parameter can be easily translated from rodent models to human patients. However, we hypothesized that the stride length is affected by the body size [6,7], which becomes a challenge in analyzing gait. Using the gait parameters assessed by CatWalk system [8–10], we examined the correlation between body-length/body-weight with stride length using CatWalk-video-derived body silhouette length. To examine the effect of growth and aging in rodents, we studied wild-type Sprague-Dawley male rats and C57BL/6N mice. Moreover, we examined the body size difference between genotypes in BACSCNA transgenic rats [11,12] and BACHD transgenic mice [13]. The CatWalk data were collected as the rodents walked freely on top of a glass-floored corridor. The rat gait was monitored at 4 different age points (10, 26, 55 and 62 weeks old), whereas the mice were monitored at 3 different age points (20, 32, and 47 weeks old). The rodent numbers included in the experiments were: (a) wild-type male rats (n=16-27/time point), (b) BACSCNA rats (n=19-32/time point), (c) wild-type mice (n=12-13/time point), and (d) BACHD mice (n=9-11/time point). The rodents were maintained under specific-pathogen-free condition. All research and animal care procedures were performed in compliance with international animal welfare standards and approved by the district governments of Lower Franconia, Würzburg, Bavaria, Germany (RegUFr#55.2-2532-2-218). The correlations between front stride length (averaged from the left and right side) and the body-silhouette-length/body-weight are shown in Figure 1. Significant correlations are shown with both body silhouette lengths and body weight. The correlation between hind stride length and body size showed the similar relationship as the front stride length (data not shown). Besides body size differences due to growth, pathological body size differences were also observed as shown in Figure 2. Thus, we demonstrated that stride length is highly correlated with body silhouette length (based on the CatWalk video) and body weight. In the near future, we need to subject gait parameters to a scaling process using body weight or silhouette length, raising the possibility of normalization for differences in size as a potential confounding of gait measure
Keywords: Stride Length; Body Size; Rodent; CatWalk

Silhouette-Length-Scaled Gait Parameters for Motor Functional Analysis in Mice and Rats - Timotius, Ivanna; Moceri, Sandra; Plank, Anne-Christine; Habermeyer, Johanna; Canneva, Fabio; Winkler, Jürgen; Klucken, Jochen; Casadei, Nicolas; Riess, Olaf; Eskofier, Björn; von Hörsten, Stephan (eNeuro, 2019)
Gait analysis of transgenic mice and rats modeling human diseases often suffers from the condition that those models exhibit genotype-driven differences in body size, weight, and length. Thus, we hypothesized that scaling by the silhouette length improves the reliability of gait analysis allowing normalization for individual body size differences. Here, we computed video-derived silhouette length and area parameters from a standard markerless gait analysis system using image-processing techniques. By using length- and area-derived data along with body weight and age, we systematically scaled individual gait parameters. We compared these different scaling approaches and report here that normalization for silhouette length improves the validity and reliability of gait analysis in general. The application of this silhouette length scaling to transgenic Huntington disease mice and Parkinson´s disease rats identifies the remaining differences reflecting more reliable, body length-independent motor functional differences. Overall, this emphasizes the need for silhouette-length-based intra-assay scaling as an improved standard approach in rodent gait analysis.<br
Keywords: CatWalk; gait; Huntington; normalization; Parkinson; scaling

Young human alpha synuclein transgenic (BAC-SNCA) mice display sex- and gene-dose-dependent phenotypic disturbances - Moceri, Sandra; Bäuerle, Natascha; Habermeyer, Johanna; Ratz-Wirsching, Veronika; Harrer, Julia; Distler, Jörg; Schulze-Krebs, Anja; Timotius, Ivanna K.; Bluhm, Alexandra; Hartlage-Rübsamen, Maike; Roßner, Steffen; Winkler, Jürgen; et al. (Behavioural Brain Research, 2024)
Parkinson's disease (PD) is a common neurodegenerative movement disorder, characterized by the loss of dopaminergic neurons in the substantia nigra pars compacta and the accumulation of aggregated alpha synuclein (aSyn). The disease often presents with early prodromal non-motor symptoms and later motor symptoms. Diagnosing PD based purely on motor symptoms is often too late for successful intervention, as a significant neuronal loss has already occurred. Furthermore, the lower prevalence of PD in females is not well understood, highlighting the need for a better understanding of the interaction between sex and aSyn, the crucial protein for PD pathogenesis. Here, we conducted a comprehensive phenotyping study in 1- to 5-month-old mice overexpressing human aSyn gene (SNCA) in a bacterial artificial chromosome (BAC-SNCA). We demonstrate a SNCA gene-dose-dependent increase of human aSyn and phosphorylated aSyn, as well as a decrease in tyrosine hydroxylase expression in BAC-SNCA mice, with more pronounced effects in male mice. Phosphorylated aSyn was already found in the dorsal motor nucleus of the vagus nerve of 2-month-old mice. This was time-wise associated with significant gait altrations in BAC-SNCA mice as early as 1 and 3 months of age using CatWalk gait analysis. Furthermore, anxiety-related behavioral tests revealed an increase in anxiety levels in male BAC-SNCA mice. Finally, 5-month-old male BAC-SNCA mice exhibited a SNCA gene-dose-dependent elevation in energy expenditure in automated home-cage monitoring. For the first time, these findings describe early-onset, sex- and gene-dose-dependent, aSyn-mediated disturbances in BAC-SNCA mice, providing a model for sex-differences, early-onset neuropathology, and prodromal symptoms of PD.
CRIS-Team Scopus Importer:2024-01-12
Keywords: Alpha synuclein; Behavioral phenotyping; Gait analysis; Parkinson's disease; Sex difference; SNCA gene-dose